Pengaruh Kinerja Perbankan Terhadap Zakat Bank Umum Syariah Di Indonesia Dan Responsitas Sosial Perusahaan - Nasution, Samsinar; Karmilasari Siregar, Ratih; Hardana, Ali; Damisa, Arti (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The percentages of banking zakat, corporate social responsibility, and return on assets varied, according to data gathered from up to nine Islamic commercial banks in Indonesia; however, increases in these areas were not always accompanied by increases in return on assets. The purpose of this study is to ascertain whether or not corporate social responsibility and banking zakat have a simultaneous or partial impact on the profitability parameters of Indonesian Islamic Commercial Banks from 2013 to 2018. The data source for this quantitative study is secondary data in the form of pooled data.